1975
DOI: 10.1346/ccmn.1975.0230308
|View full text |Cite
|
Sign up to set email alerts
|

Isomorphous Substitution of Iron for Aluminium in Some Soil Kaolinites

Abstract: Abstract--Clay ( < 2 ttm) and fine silt (~20/~m) fractions of twenty seven soil samples from eight tropical ferruginous profiles of the Mysore Plateau (India) were analysed for kaolinite by dehydroxylation and selective dissolution. The considerable amounts of iron extracted by the procedure and the closeness of the SiO2/R203 molar ratios (2.00-2.18) to the ideal value of 2.00 indicated that iron was a structural constituent of the kaolinites, The calculated unit cell cation composition of the kaolinites showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 24 publications
2
9
0
2
Order By: Relevance
“…This value is significantly smaller than that of Rengasamy et al (1975), and is closer to the 0.075 ~ value, measured by Russell & Clark (1978) for Fe 3+ in octahedral sites of nontronite, and to 0-087 ~ for Fe and Mg substitutions in smectites (Desprairies, 1983). IR spectroscopy confirms increasing Fe for AI substitution in kaolinite with increasing (a) of the starting glass.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This value is significantly smaller than that of Rengasamy et al (1975), and is closer to the 0.075 ~ value, measured by Russell & Clark (1978) for Fe 3+ in octahedral sites of nontronite, and to 0-087 ~ for Fe and Mg substitutions in smectites (Desprairies, 1983). IR spectroscopy confirms increasing Fe for AI substitution in kaolinite with increasing (a) of the starting glass.…”
Section: Discussionsupporting
confidence: 80%
“…Because of the low Fe content of natural and previously synthesized kaolinites, variations in b-parameter measurements were generally not significant and beyond the resolution of the method (Calvert, 1981). For natural kaolinites with expected higher Fe contents, Rengasamy et al (1975) observed an increase in the b-parameter of 0-312 • per substituted Fe 3+ atom but this value is questionable (Herbillon et al, 1976;Calvert, 1981). Because of the way cations are allocated to octahedral positions, Rengasamy et al (1975) have probably overestimated the structural Fe content.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Copyright 9 1983, The Clay Minerals Society microprobe (e.g., Jepson and Rowse, 1975), chemical (e.g., Rengasamy et al, 1975), electron spin resonance (ESR) (e.g., Meads and Malden, 1975), and infrared (Mendelovici et al, 1979) studies. The considerable number of studies employing ESR techniques have recently been reviewed by Hall (1980).…”
Section: The Nature Of the Iron Associated With Kaolinmentioning
confidence: 99%
“…Clearly, kaolin group minerals are able to accommodate structural Cr so that retention of some Cr in kaolinite formed from muscovite could be anticipated. Similarly, kaolin group minerals may accommodate substantial amounts of structural Fe (Rengasamy et aL, 1975;Herbillon et al, 1976).…”
Section: Retention O F Elementsmentioning
confidence: 99%